Genomic analysis of mycobacterium abscessus strain M139, which has an ambiguous subspecies taxonomic position - Ngeow, Y.F.; Wee, W.Y.; Wong, Y.L.; Tan, J.L.; Ongi, C.S.; Ng, K.P.; Choo, S.W. (2012)
Mycobacterium abscessus is a ubiquitous, rapidly growing species of nontuberculous mycobacteria that colonizes organic surfaces and is frequently associated with opportunistic infections in humans. We report here the draft genome sequence of Mycobacterium abscessus strain M139, which shows genomic features reported to be characteristic of both Mycobacterium abscessus subsp. abscessus and Mycobacterium abscessus subsp. massiliense.